2021
DOI: 10.34293/education.v9i3.3907
|View full text |Cite
|
Sign up to set email alerts
|

Augmented Reality in Science Education: An Application in Higher Education

Abstract: Effective usage of augmented reality(AR) depends on good integration into the learning environment. Based on a qualitative research approach, this study investigates the effects of using AR technologies in science education to support the effective use of AR. Students’ experiences of AR were gathered using a prepared questionnaire form. Within the scope of science education, AR was used in a university-level chemistry course. Using theme analysis, descriptive themes were created by analyzing the content of com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 27 publications
(49 reference statements)
1
18
0
4
Order By: Relevance
“…The many abstract science concepts that are difficult for students to understand could be understood using AR. Previous studies found that AR effectively explained abstract concepts (Karagozlu & Ozdamli, 2017) and material difficult for students to visualise, improving their imagination skills (Yilmaz, 2021). The application of AR in the learning process has many benefits.…”
Section: Teachers' Interest In Implementing Ar In Science Learningmentioning
confidence: 99%
“…The many abstract science concepts that are difficult for students to understand could be understood using AR. Previous studies found that AR effectively explained abstract concepts (Karagozlu & Ozdamli, 2017) and material difficult for students to visualise, improving their imagination skills (Yilmaz, 2021). The application of AR in the learning process has many benefits.…”
Section: Teachers' Interest In Implementing Ar In Science Learningmentioning
confidence: 99%
“…Many science concepts that are difficult for students could be understood using augmented reality technology. Previous studies found that it effectively explained abstract concepts (Karagozlu & Ozdamli, 2017) and material difficult for students to visualize, improving their imagination skills (Yilmaz, 2021). The application of augmented reality in the learning process has many benefits in education.…”
Section: Students' Opinion On Mobile Ar In Learning Physicsmentioning
confidence: 99%
“…All problems experienced by students can be overcome by implementing augmented reality in the learning process. Augmented reality allows students to explore concepts that are not visible to the naked eye and make them visible (Yilmaz, 2021) and it displays real objects that have never been seen before (Guntur & Setyaningrum, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Based on the results of the analysis that has been carried out on student perceptions regarding the characteristics of the material in the optics course, it can be concluded that some material such as in module 3 in KB 2 regarding the optical system of the eye is still difficult to understand, and requires visualization to understand the material, namely AR media. In various research, AR has been used in various fields including education, medicine, pilot training, engineering, and others (Yilmaz, 2021). The use of Augmented Reality media has the potential to increase the efficiency of learning and reduce misconceptions in understanding material (Febrianti et al, 2017).…”
Section: Understanding Of Student Concepts In the Materials Of Eye Op...mentioning
confidence: 99%